The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/smll.202207593
|View full text |Cite
|
Sign up to set email alerts
|

Key Role of Choline Head Groups in Large Unilamellar Phospholipid Vesicles for the Interaction with and Rupture by Silica Nanoparticles

Abstract: For highly abundant silica nanomaterials, detrimental effects on proteins and phospholipids are postulated as critical molecular initiating events that involve hydrogen‐bonding, hydrophobic, and/or hydrophilic interactions. Here, large unilamellar vesicles with various well‐defined phospholipid compositions are used as biomimetic models to recapitulate membranolysis, a process known to be induced by silica nanoparticles in human cells. Differential analysis of the dominant phospholipids determined in membranes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 73 publications
(132 reference statements)
0
2
0
Order By: Relevance
“…In fact, no correlation between ROS generation and membranolytic activity was often observed [ 3b,10a,36 ] but a large panel of silica and silica‐based materials confirmed the central role of NFS in the establishment of specific interactions with zwitterionic phospholipids in cell membranes. [ 10b,37 ] To measure this interaction, we used non‐internalizing cells (red blood cells, RBC) that limit the potential interaction with particles to the outer lipid bilayer of their cytoplasmatic membrane. RBC does not have a role in the inflammatory or fibrotic responses induced by quartz particles, but their membrane is a convenient model [ 38 ] and the hemolysis test is largely used to evaluate the pro‐inflammatory activity of quartz dust.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, no correlation between ROS generation and membranolytic activity was often observed [ 3b,10a,36 ] but a large panel of silica and silica‐based materials confirmed the central role of NFS in the establishment of specific interactions with zwitterionic phospholipids in cell membranes. [ 10b,37 ] To measure this interaction, we used non‐internalizing cells (red blood cells, RBC) that limit the potential interaction with particles to the outer lipid bilayer of their cytoplasmatic membrane. RBC does not have a role in the inflammatory or fibrotic responses induced by quartz particles, but their membrane is a convenient model [ 38 ] and the hemolysis test is largely used to evaluate the pro‐inflammatory activity of quartz dust.…”
Section: Resultsmentioning
confidence: 99%
“…Lysosomal membrane perturbation leads to the activation of the inflammasome machinery that triggers the maturation and release of pro-inflammatory interleukins, including interleukin IL-1β and IL-18 (Figure 12B) [97,98]. Silica cytotoxicity and haemolysis correlated well with the available external surface area of the particles [99,100], suggesting that, for SiO 2 , the particle surface rules the interaction with biomembrane.…”
Section: Interaction With Cell Membrane Models (Eg Red Blood Cells An...mentioning
confidence: 96%
“…Several particle physico-chemical parameters, including size, shape, agglomeration/aggregation state, and differences in surface chemistry (e.g., surface hydrophilicity/hydrophobicity and charge), have been reported to influence the interaction with model membranes [122]. Several studies demonstrated that crystalline and amorphous SiO 2 (nano)particles may destabilize zwitterionic vesicles of phosphatidylcholine (PC) lipids in different size ranges [26,100,[123][124][125][126]. The same effects have been observed for colloidal and pyrogenic nanosilica interacting with mixed vesicles which mimic the PL composition of lung cells [100].…”
Section: Figure 12mentioning
confidence: 99%
See 1 more Smart Citation
“…Because synthetic small unilamellar vesicles (SUVs) and supported lipid bilayers (SLBs) make the structural and chemical control of model membranes much simpler, they are often used as model systems of cell membranes to study fundamental biophysical processes. 12,13 Many recent studies have reported interactions between GOFNs and SLBs. Li et al suggested that the attachment of GO to membranes was promoted by hydrogen bonding by using SLBs.…”
Section: Introductionmentioning
confidence: 99%